2020
DOI: 10.1302/0301-620x.102b11.bjj-2020-0578.r1
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparison of functional outcomes of primary reverse shoulder arthroplasty for acute fractures versus rotator cuff deficiencies

Abstract: Aims The purpose of this study was to determine whether there were long-term differences in outcomes of reverse shoulder arthroplasty (RSA) undertaken for acute proximal humeral fracture versus rotator cuff deficiency with a minimum follow-up of five years. Methods This was a prospective cohort study comparing 67 patients with acute complex proximal humeral fracture and 64 patients with irreparable rotator cuff deficiency who underwent primary RSA. In the fracture group, there were 52 (77.6%) females and 15 (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Existing studies rarely report post-surgical complications stratified by indication. Sebastia-Forcada et al 's prospective series [8] reported no significant difference in long-term complication rate or 10-year arthroplasty survival between RSA for fracture or for arthropathy. We recognize the higher-than-expected complication rate in the arthritis group in our study.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Existing studies rarely report post-surgical complications stratified by indication. Sebastia-Forcada et al 's prospective series [8] reported no significant difference in long-term complication rate or 10-year arthroplasty survival between RSA for fracture or for arthropathy. We recognize the higher-than-expected complication rate in the arthritis group in our study.…”
Section: Discussionmentioning
confidence: 94%
“…They found that, although RSA provided significant within-group improvements in all outcomes regardless of indication, the acute PHF and PHF sequelae groups consistently showed significantly lower postoperative means of all four standard planes of shoulder motion, as well as lower patient-reported outcome measures (ASES and Constant shoulder), than the groups with GHOA or massive cuff tear with or without GHOA or CTA. Conversely, one of the few long-term prospective studies on RSA for acute fractures versus rotator cuff deficiencies in the elderly, by Sebastia-Forcada et al [8], showed no significant differences in mean functional scores or ranges of shoulder motion at the end of a mean 8.4 years of follow-up.…”
Section: Discussionmentioning
confidence: 95%
“…Two studies report no difference in final aROM or patient reported outcomes scores. 9,10 One study reports a difference in forward elevation, as well as early differences in functional scores which become equivalent around 6 months to 1 year. 11 Two describe a statistical difference in aROM and patient reported outcomes only in chronic fracture sequela subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, these patients have a better outcome than those who had the RSA implanted because of a fracture and in whom the tuberosities have been refixed. 12 - 14 Recent studies on RSA in proximal humerus fracture show improved stability of the tuberosity construct and no functional disadvantage after excision of the tendon. Furthermore, this allows for better intraoperative visualization of the glenoid, enabling even more precise implant positioning.…”
Section: Introductionmentioning
confidence: 99%